Diagnostic criteria for spinal muscular atrophy 5q - I. V. Sharkova; E. L. Dadali; S. S. Nikitin (Нервно-мышечные болезни)
Background. The variety of phenotypic manifestations of spinal muscular atrophy 5q (5qCMA) is the reason for the difficulty in diagnosing and delaying the diagnosis, which is of particular importance today due to the emergence of new etiopathogenetic therapeutic possibilities.Objective: determination of the main clinical features and symptoms of 5qCMA with onset at different age periods, and the development of an algorithm that can help in making decisions regarding the need for testing the SMN1 gene by primary care and hospital doctors.Materials and methods. A retrospective analysis of the case histories of patients observed at the Research Center of Medical Genetics with a confirmed diagnosis of 5qCMA was carried out.Results. The study included data from 315 patients, including: 173 with type I, 95 and 47 with types II and III 5qCMA. In all cases, the presence and diagnostic significance of 27 signs and symptoms were analyzed, depending on the age of disease manifestation. An attempt was made to isolate the main symptoms, which are the basis for the mandatory exclusion of 5qCMA by molecular genetic methods in patients with the onset of the disease before and after 18 months of life.